UJI VIABILITAS DAN ANALISIS PERTUMBUHAN PADI LOKAL (Oryza sativa L.) DENGAN PERLAKUAN BERBAGAI KOSENTRASI PHOLYETHYLENE GLYCOL (PEG) 6000 - Haerani A Mayasari Irianti; rosmala widijastuti; Nurhening Yuni Ekowati (Musamus University, 2020)
Indonesia is a country that has a wealth of germplasm diversity. One of the potential of germplasm in Indonesia which is quite a lot and diverse is rice plants. Increased rice production is increasingly needed given the increasing need for rice consumption and population. One of the main factors that determine the success of increasing production in rice cultivation is rice seeds. The availability of quality seeds causes the plants produced have good quality and high production levels. Some things that can cause a decrease in the quality of seeds is the water content that is not right during the storage period.One way that is often used to increase seed vigor is by invigoration treatment. One of the compounds commonly used in research for invigoration treatment is Polyethylene glycol (PEG). The local rice plant that grows in Merauke according to farmers' information is Palenok. This rice grows and develops in swamps. The purpose of this study was to analyze the effect of various concentrations of PEG 6000 on the viability and growth of local rice seeds. This research was carried out at the Agrotechnology Laboratory and the Agrotechnology Screen House of Musamus Merauke University, from July to October 2018. Presentation and analysis of the data in this study was conducted descriptively. The results showed that the PEG 6000 concentration of 15% (P3) treatment gave the best average for germination parameters and for plant growth parameters the PEG 6000 0% (P0) treatment gave the best average for parameters of plant height, number of leaves and number of tillers. Keywords: viability; local rice; Polyethylene glycol (PEG) 6000